Analisa Tipe Kepemimpinan Pembina Asrama Putri IAKN Tarutung - Grace Na Anantha Lumban Tobing; Rike Yohana Simatupang; Ibelala Gea (Jurnal Teologi Injili dan Pendidikan Agama, 2023)
. The type of leadership will be synonymous with the leadership style of someone carrying out a leadership. Thus it is clear that leadership is a person's ability to influence other people to work together to achieve the goals that have been aspired to. And every coach in a hostel has a different type of leadership. The results of this study show that the leadership type of the hostel supervisor is very important to be discussed for the sake of comfort between the supervisor and the hostel children. This study used a qualitative method by collecting several sources from existing books and journals. So the purpose of this study is to enable someone to know the type of leadership of each coach in the dormitory, because many coaches now ignore their leadership type.